ANALISIS KUALITAS DAN KUANTITAS GURU PAUD DI INDONESIA - Hasti Utami; Lilis Kholisoh Nuryani; Sumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the quality and quantity of Early Childhood Education (PAUD) teachers in Indonesia. Teacher quality is measured through academic qualifications and pedagogical competence, while quantity is measured based on the ratio of teachers to children and the distribution of teachers between regions. The research method used is qualitative descriptive analysis by utilizing secondary data from the Ministry of Education and Culture and other relevant sources. The quantity of early childhood education institutions in Indonesia is growing rapidly. This increase occurs along with the large number of early childhood (AUD) that must be served. The quantity is directly proportional to the need for quality teachers. The demand for quality educators is increasingly clear by returning early childhood development as a golden age so that a good foundation from quality teachers has an impact on the excellence of the Indonesian nation's generation. For this reason, PAUD educators are needed who understand the opportunities for maximizing this from an early age. There needs to be an effort to improve the quality of education services for early childhood by improving the quality of early childhood educators.The results of the study are expected to provide a comprehensive picture of the current condition of the quality and quantity of PAUD teachers in Indonesia, identify existing gaps, and provide policy implications for improving the quality and fulfillment of PAUD teacher needs in order to realize quality and equitable PAUD throughout Indonesia.